2008
DOI: 10.1002/jpln.200700330
|View full text |Cite
|
Sign up to set email alerts
|

Capacity, selectivity, and reversibility for nitrate exchange of a layered double‐hydroxide (LDH) mineral in simulated soil solutions and in soil

Abstract: The leaching of nitrate is an important way of N losses from agricultural soils in humid regions. Nitrate leaching is difficult to control as most soils under crop production do not have anionexchange properties, and nitrate remains mobile in the solution. The present work evaluated the potential use of a synthetic layered double-hydroxide (LDH) mineral as a nitrate exchanger in soil. The LDH used was a chloride form of a magnesium-aluminum layered double hydroxide with the formula: [Mg 2+ 0.82 Al 3+ 0.18 (OH)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 14 publications
1
14
0
Order By: Relevance
“…Ca-Al-NO 3 LDHs is synthesized by using a co-precipitation method because of its facile and low cost features. In order to promote the real scale engineering application, LDHs are prepared under ambient conditions [33,[46][47][48]. However, in the present study, the pH value of the solution is changed to prepare LDH nano-platelets with different sizes.…”
Section: Preparation and Characterization Of The Ca-al-no 3 -Ldhsmentioning
confidence: 97%
“…Ca-Al-NO 3 LDHs is synthesized by using a co-precipitation method because of its facile and low cost features. In order to promote the real scale engineering application, LDHs are prepared under ambient conditions [33,[46][47][48]. However, in the present study, the pH value of the solution is changed to prepare LDH nano-platelets with different sizes.…”
Section: Preparation and Characterization Of The Ca-al-no 3 -Ldhsmentioning
confidence: 97%
“…Studies have reported the use of LDH as slow release source of nutrients to plants. Torres-Dorante et al (2008) studied the potential use of MgAl-Cl-LDH, as a NO − 3 adsorber in soils, controlling its losses and availability. It was examined the adsorption capacity of NO − 3 by LDH in aqueous solution as well as anion adsorption selectivity.…”
Section: Source Of Nutrient Storage and Controlled Release For Plantsmentioning
confidence: 99%
“…Actually, some studies have reported the potential use of LDHs as adsorbents or reservoirs of nitrate. [9,10,[13][14][15][16][17][18] However, the selectivity of LDHs for nitrate is generally considered not to be high, and a large number of studies have reported that anions with a higher charge density tend to be more preferentially intercalated into LDHs. [6][7][8]19,20] According to a report by Miyata, [19] the order of exchange selectivity for monovalent anions in the case of Mg-Al LDHs (Mg/ Al = 2.3) is OH -> F -> Cl -> Br -> NO 3 -> I -, and according to a report by Costa et al, [20] the order of exchange selectivity based on a computational simulation with Zn-Al LDHs (Zn/Al = 2) is CO 3 2-> OH -> F -> Cl -> Br -> NO 3 -.…”
Section: Introductionmentioning
confidence: 99%